Into the Mummy's Tomb - Reeves, Nicholas; Nang Chan Yeema (New York, USA Scholastic Inc., 1992)
An account of Howard Carter's discovery of the tomb of King Tutankhamun, descriptions of the artifacts inside and their importance, the discovery in 1988 of more artifacts, and theories about the curse associated with the tomb.
Keywords: Adult Nonfiction